Optimering av informationsflöde och analys av kognitiv ergonomi: vid CHARM:s organisation - Magnusson, Mathilda; Lilja, Palita (My University, 2023)
This work was carried out at the Chalmers Student Union at Chalmers University of Technology with a focus on information flows and cognitive load within CHARM (Chalmers Studentkårs Arbetsmarknadsdagar), an organization that runs one of Scandinavia's largest job fairs. The fair offers about 160 companies the opportunity to meet more than 13,000 students who are seeking employment and degree projects. CHARM is entirely run by students, with a project manager and committee members who are students at Chalmers, working on preparations for the job fair held every year in February. The research questions aim to identify the current information flow and investigate potential improvements to alleviate cognitive load for the organization's members. The work has focused on CHARM's internal work processes and activities, with the main emphasis being on the development of an interface for a digital tool, resulting in a prototype named MindEase, aimed at optimizing CHARM's operations, increasing productivity, and promoting the well-being of committee members. The limitations that the work has followed have been focused solely on the CHARM committee members' work processes and activities, without considering the organization's outward-facing activities towards visiting students or how they perceive the organization. The results show that there are deficiencies in the current information flow and that an optimized information flow has the potential to improve it, and that a targeted information flow can create positive changes in sustainability efforts and workplace efficiency. The report is written in Swedish.
Keywords: Informationsflöde, Kognitiv ergonomi, Gränssnitt, Mässa, Stress, Belastning, Organisation, Digitalt verktyg, Kommunikation.